(untitled) (Philology, 2026)
In 1990, Paulina Chiziane published the first novel written by a woman in Mozambique. The work of the contemporary Mozambican author is often seen as a mission as regards the central position of the female characters and social problems. The present study is aimed at placing Chiziane’s novels in the context of the historical development of the literary writing in Mozambique, highlighting the main genre and aesthetic preferences and pointing out the main topics, motifs and figures because of which they belong to the literary heritage of the African Portuguese-speaking country. The comparative overview contributes to knowing better, in the literary studies’ context in Bulgaria, the Mozambican literature, giving a panoramic view of the particulars and logic of the evolutionary processes and creating a basis not only for its independent study, but also for larger comparative interpretations.